Optimalisasi Kinerja Pelayanan Angkutan Pedesaan di Kabupaten Kudus - Nada Agi Andhini; Tatang Adhiatna; Arnita Aprilia Aprilia (Sekolah Tinggi Teknik - PLN, 2021)
The existence of public transportation is important in supporting community activities in Kudus Regency. The provision of public transportation should be able to facilitate community activities, but there are obstacles that complicate community activities such as low transportation load factors, fleet numbers, and the existence of trays that do not work according to the line. The purpose of the study is to find out the performance of public transportation in Kudus Regency. Public transport performance analysis seen in terms of passengers, government and operators and analysis of fleet needs using public transport performance survey. The primary data analysis required is the vehicle's operating rate, vehicle frequency, headway, wait time, load factor, and vehicle operating costs through direct observation in the field. While the secondary data used the number of fleets and maps of rural transport route networks was taken from the SK Pemkab Kudus 2019. Based on the results of the analysis conducted showed that it was found to be 70% or in the category of quite high fleet operations and 100% of the level of inequality that is on both routes (Jati-Singocandi, and Jati-Karangmalang). This causes the existing condition of the performance of rural transportation services in Kudus Regency including into bad conditions.